Multi-timescale dynamics of extreme river flood and storm surge interactions in relation with large-scale atmospheric circulation: Case of the Seine estuary. (5th July 2023) - Turki, E.I.; Deloffre, J.; Lecoq, N.; Gilbert, R.; Mendoza, E.T.; Laignel, B.; Salameh, E.; Gutierrez Barcelo, A.D.; Fournier, M.; Massei, N.
Abstract: The present work investigates the multi-timescale dynamics of extreme fluvial-surge interactions (EFS ) in a river-tide environment, in the case of the Seine estuary. This environment is considered an excellent natural laboratory to analyze river-surge interaction because of its time-varying flow and the available water-level records provided by tide gauges along the estuary. A spectral approach has been used to investigate the multi-timescale changes in EFS, governed by fluvial and marine contributions, in relation to the historical events of flood-storm concomitance and the large-scale atmospheric circulation. The spectral components of EFS, calculated at five stations along the estuary, highlighted a series of variability modes varying from the inter-month (∼3–6 months) to the inter-annual (∼2-, ∼3-5- and ∼6-8-years) scales and exhibiting, respectively, 55% and 20% of the total variability. The contribution of marine and fluvial effects in the EFS varies along the estuary and according to the timescale from seasons, when the interaction is governed by tidal deformation, to years. The connection of the historical flood-storm events with the EFS signal changes in their spectral signature according to their severity as well as the energetic physical drivers acting in each event: events with high return period are manifested at larger scales while events with low return period are limited to small scales. Finally, the examination of the physical relationships between the EFS and the global climate mechanisms has demonstrated the key role of the Sea Level Pressure (SLP) and the North Atlantic Oscillation (NAO) acting, respectively, in anti-phase at ∼1-2-yr and in phase at scales larger than 3-yr. The signature of the climate drivers operates differently according to the timescale; they are identified within the ∼80% of the inter-annual EFS . This signature is more significative since the 2000s when the increase in the NAO generates a rise in EFS variability. ∼20% of EFS would be related to the non-linear effects of the timescale interactions and other local mechanisms operating at such scales. This finding highlights the non-stationarity of the multi-timescale dynamics of marine storms and fluvial floods, and the relevance of the climate connection use for assessing the compound multi-hazard events at large-scales. Graphical abstract: Image 1 Highlights: Estuarine flood-surge interactions change at intermonthly and interannual scales. Flooding compound events are related to the timescales according to their severity. Large-scale variability is linked to the climate mechanisms of SLP and NAO.